Assessing in-session rumination during CBT for depression: Replication and further evaluation of an observational measure - J.C. Kennedy; B.W. Dunlop; S.E. Baldwin; C.J. Liu; H.S. Mayberg; W.E. Craighead (Journal of Mood and Anxiety Disorders, 2024)
This study sought to further evaluate an observational measure of rumination that occurs during psychotherapy (i.e., in-session rumination). Specifically, the study aimed to replicate the reliability of an observational rating procedure in new therapy sessions and a new sample, clarify the relationship between in-session rumination and depressive symptoms, and evaluate for the first time the relationship between in-session rumination and self-reported rumination. A team of trained research assistants produced observational ratings of in-session rumination occurring during video-taped sessions of CBT from two separate treatment studies. Thirty-five patients with major depressive disorder (MDD) from one study had their final session rated, and 17 patients with MDD from another study had their first session rated. Results showed that the observational ratings were reliable, and that in-session rumination generally correlated with depressive symptom severity as expected, with higher in-session rumination predicting higher depressive symptom levels both cross-sectionally and longitudinally. Preliminary evidence also found that in-session rumination correlated with self-reported rumination, and exploratory analyses provided preliminary evidence supporting the incremental validity of in-session rumination for predicting depression severity after treatment. The results indicate that in-session rumination can be reliably identified during CBT sessions and consistently predicts higher depressive severity, both of which support efforts to develop treatments that specifically target rumination.